2010
DOI: 10.1007/s10103-010-0874-x
|View full text |Cite
|
Sign up to set email alerts
|

Low-level laser therapy (LLLT) acts as cAMP-elevating agent in acute respiratory distress syndrome

Abstract: The aim of this work was to investigate if the low-level laser therapy (LLLT) on acute lung inflammation (ALI) induced by lipopolysaccharide (LPS) is linked to tumor necrosis factor (TNF) in alveolar macrophages (AM) from bronchoalveolar lavage fluid (BALF) of mice. LLLT has been reported to actuate positively for relieving the late and early symptoms of airway and lung inflammation. It is not known if the increased TNF mRNA expression and dysfunction of cAMP generation observed in ALI can be influenced by LLL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 33 publications
1
35
0
2
Order By: Relevance
“…Several workers have shown an increase in adenosine-3’,5’-cyclic-monophosphate (cAMP) after PBM [54], [55]. Although it is tempting to suppose that this increase in cAMP is a direct consequence of the rise in ATP caused by light, firm evidence for this connection is lacking.…”
Section: Molecular Mechanisms Of Pbmmentioning
confidence: 99%
“…Several workers have shown an increase in adenosine-3’,5’-cyclic-monophosphate (cAMP) after PBM [54], [55]. Although it is tempting to suppose that this increase in cAMP is a direct consequence of the rise in ATP caused by light, firm evidence for this connection is lacking.…”
Section: Molecular Mechanisms Of Pbmmentioning
confidence: 99%
“…BDNF promotes the survival of neurons and dendrite growth both in vitro and in vivo (Katz and Shatz, 1996;Connor and Dragunow, 1998;Murer et al, 2001). A growing body of evidence indicates that BDNF levels are decreased in brains of AD patients (Hu and Russek, 2008;Zuccato and Cattaneo, 2009) and APP transgenic mice .…”
Section: Lllt Increases Bdnf Protein Levels In Hippocampal Neuronsmentioning
confidence: 99%
“…In addition to their classical role in supporting survival of neuronal populations, brain-derived neurotrophic factor (BDNF), in particular, is a strong candidate to modulate dendritic structure and potentiate synaptic transmission in the CNS (Katz and Shatz, 1996;Connor and Dragunow, 1998;Murer et al, 2001). In patients with AD, neurites atrophy and synaptic loss are considered the major causes of cognitive impairment (Einstein et al, 1994;Masliah et al, 2001;Selkoe, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive effects of LLLT in the modulation of the inflammatory process were also demonstrated by Oliveira et al [35] in the experimental model of sepsis induced by lipopolysaccharide. de Lima et al [36] also demonstrated a positive effect of LLLT on the inflammatory process in the same model of sepsis.…”
Section: Discussionmentioning
confidence: 89%